Faktor-Faktor Yang Mempengaruhi Kontribusi Peserta Pada Perusahaan Asuransi Jiwa Syariah di Indonesia - Risma Kartika Mulya Wardhani; Dina Fitrisia Septiarini (Universitas Airlangga, 2017)
The aims of this study is to determine the effect of operating costs, investment and claims partially and simultaneously against the contribution to the shariah life insurance companies in Indonesia during 2013-2015. This study uses quantitative approach. The sampling technique is purposive sampling and there were 19 shariah life insurance company as subjects. The technique used is regression analysis using fixed effect model (FEM) panel data. The results study indicate that the operating expenses, investment returns and claims partially and simultaneously are significant and have positive impact on the contribution to the KP equation=67051.80+0,578102BO+2,605768HI+1,427397KLM. The results illustrate that the number of contributions have important influence in the operations of the companies. The amount of contributions received is expected to cover the costs incurred for the company's operations, they can be invested so as to achieve the company's expected return, and to pay claims.